Revenge pornography: Criminological and criminal law aspects - Dimovski Darko (Zbornik Radova Pravnog Fakulteta u Nišu, 2023)
The propensity to violence is inherent in every society. The development and growing use of modern technologies has lately provided another instrument for victimization of women on an unprecedented scale. This instrument is reflected in the emergence of deepfake and revenge porn as new forms of violence against women. The subject matter of analysis in this paper is revenge pornography, which will be observed from the criminological and criminal law perspectives. In the first part of the paper, after presenting the definition of the concept of revenge pornography, the author elaborates on the key characteristics of revenge pornography as an instrument for the victimization of women. The second part of the paper provides an overview of the normative solutions on this subject matter in certain countries. Given the fact that revenge pornography has been the subject matter of analysis of the European Court of Human Rights in Strasbourg, the author analyzes the ECtHR case law on this issue. In the next part, the author presents the normative framework on this issue in the Republic of Serbia, viewed through the prism of revenge pornography. The final part of the paper focuses on the fight against revenge pornography, with the aim of providing adequate protection to female victims of this criminal offence. It is the only way to increase women's security and confidence that state bodies will provide adequate protection against the misuse of modern technologies.